Longitudinal and transverse spin transfer to Λ and ¯Λ hyperons in polarized p+p collisions at √𝑠 = 200 GeV - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review, 2024)
The longitudinal and transverse spin transfers to Λ (¯Λ) hyperons in polarized proton-proton collisions are expected to be sensitive to the helicity and transversity distributions, respectively, of (anti)strange quarks in the proton, and to the corresponding polarized fragmentation functions. We report improved measurements of the longitudinal spin transfer coefficient, 𝐷𝐿⁢𝐿, and the transverse spin transfer coefficient, 𝐷𝑇⁢𝑇, to Λ and ¯Λ in polarized proton-proton collisions at √𝑠=200 GeV by the STAR experiment at RHIC. The dataset includes longitudinally polarized proton-proton collisions with an integrated luminosity of 52 pb−1, and transversely polarized proton-proton collisions with a similar integrated luminosity. Both datasets have about twice the statistics of previous results and cover a kinematic range of |𝜂Λ⁡(¯Λ)|<1.2 and transverse momentum 𝑝𝑇,Λ⁡(¯Λ) up to 8 GeV/𝑐. We also report the first measurements of the hyperon spin transfer coefficients 𝐷𝐿⁢𝐿 and 𝐷𝑇⁢𝑇 as a function of the fractional jet momentum 𝑧 carried by the hyperon, which can provide more direct constraints on the polarized fragmentation functions.